Paediatrician beliefs and practices around influenza vaccination - Newcombe, J.; Kaur, R.; Wood, N.; Seale, H.; Palasanthiran, P.; Snelling, Thomas (Wiley-Blackwell Publishing Ltd., 2017)
Aim: The uptake of influenza vaccination in children with high-risk medical conditions continues to be low in Australia and internationally. We aimed to determine Australian paediatricians’ beliefs and practices around the influenza vaccination of children. Methods: This was conducted as a cross sectional survey of paediatricians from two tertiary paediatric hospitals in Sydney. Results: There were 101 participants. Influenza vaccination was not prioritised compared with other vaccines and clinical issues, with fewer than half of respondents strongly agreeing that influenza vaccination was useful. Paediatricians’ knowledge of guidelines and recommendations in this area was suboptimal. Interventions thought most likely to improve vaccine coverage included better education of doctors, greater vaccine availability in outpatient clinics and automated reminder systems. Conclusion: The inclusion of influenza vaccine on the standard Australian immunisation schedule may be required to improve vaccine coverage in high-risk children.